Gene-environment interactions in complex disease - Franks, Paul (Henry Stewart Talks, 2013)
Definition of gene-environment interaction, Examples of interactions and rationale, Why do we think gene x environment interactions might exist for complex, multifactorial traits?, How might gene x environment interactions be detected?, Limitations of many existing studies of gene x environment interactions, Gene x lifestyle interaction on type 2 diabetes incidence, Genotype-based recall randomized clinical trials, What are the likely mechanisms underlying gene x environment interactions?